P3.028 Positivity Rate of Chlamydia Trachomatis and Status Quo of Opportunistic Screening in Germany. (13th July 2013) - Dudareva-Vizule, S; Sailer, A; Hamouda, O; Bremer, V
Abstract : Background: Chlamydia trachomatis (CT) infections are not reportable in Germany and limited data on CT-prevalence among women is available. In 2008 an opportunistic CT screening programme for women < 25 years (OCS) was introduced. We assessed positivity rate of CT-infection and evaluated the OCS in order to develop recommendations to improve OCS. Methods: In September 2010 voluntary laboratory-based sentinel surveillance system was implemented and is collecting retrospective (from 2008) and prospective data on performed CT-tests together with results and information on age and test reason (TR). We calculated positivity rates (PR) by age and TR and compared them with Chi 2 test. We described data by time and estimated the proportion of the target population reached by OCS. Results: As of 27.11.2012 data from 14 laboratories were available for analysis. These data cover approximately 25% of all CT-tests performed in Germany. Overall 90.6% (643, 332) of all tests (710, 021) were among women. Among those 19.1% (122, 650) were attributable to OCS, 31.3% (201, 322) to screening in pregnancy (CSP), 30.6% (197, 013) to diagnostic test (DT), and in 19.0% (122, 347) the TR was not known. The number of OCS-tests increased by 114% in 2009, 15% in 2010, and 7% in 2011 compared to the previous year. Extrapolating, OCS covered 10% of the target population. OCS PR was 5.3%, higher than for other TR (2.6% among CSP, and 3.9% among DT, p-value < 0.001). OCS PR was highest in women aged 15–19 years (7.1%) and 20–24 (6.5%) compared to other age-groups (p-value < 0.001). Conclusion: The proportion of young women testing positive for CT was high. OCS coverage in Germany is insufficient and did not increase substantially in the last years. OCS should be promoted among the target population and physicians. Awareness campaigns for young women should be implemented. Respective regulations should be expanded and remuneration to physicians for OCS offered.